2011
DOI: 10.1007/s00723-011-0276-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aprotic Solvents on the Transmission of Anomalous Substituent Effects on 13C NMR Chemical Shifts at the Carboxyl Carbon (δco) in Meta-Substituted Benzoic Acids: A Strong Evidence for π-Polarization Mechanism

Abstract: Anomalous (reverse) substituent-induced 13 C nuclear magnetic resonance chemical shifts at the carboxyl carbon (d co ) in meta-substituted benzoic acids have been studied for 11 substituents having varying electronic effects in 4 aprotic (nonhydroxylic) solvents of varying polarity by employing different dual substituent parameter models. The regression results for apolar aprotic solvents provide a strong evidence for through space p-polarization mode of transmission of reverse metasubstituent effects on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The results of solvent effects on δ co of substituted benzoic acids provide a strong evidence for the through‐space π‐polarization mode of transmission of reverse substituent effects on the carboxyl carbon in benzoic acids. The results also show that an apolar aprotic solvent is a distinct preference over a dipolar aprotic one for investigating intrinsic effects of substituents on 13 C chemical shifts at the side chain or ring carbon centers (δ c ) in benzoic acids and other aromatic molecules . The study has shown, in particular, that the transmission of the anomalous (reverse) effect of an m ‐substituent on δ co in benzoic acid molecule can be successfully interpreted by a 5.5:−2.5:1 combination of the localized, extended, and resonance‐induced π‐polarization mechanisms …”
Section: C Nuclear Magnetic Resonance Chemical Shift Of the Carbonymentioning
confidence: 71%
See 3 more Smart Citations
“…The results of solvent effects on δ co of substituted benzoic acids provide a strong evidence for the through‐space π‐polarization mode of transmission of reverse substituent effects on the carboxyl carbon in benzoic acids. The results also show that an apolar aprotic solvent is a distinct preference over a dipolar aprotic one for investigating intrinsic effects of substituents on 13 C chemical shifts at the side chain or ring carbon centers (δ c ) in benzoic acids and other aromatic molecules . The study has shown, in particular, that the transmission of the anomalous (reverse) effect of an m ‐substituent on δ co in benzoic acid molecule can be successfully interpreted by a 5.5:−2.5:1 combination of the localized, extended, and resonance‐induced π‐polarization mechanisms …”
Section: C Nuclear Magnetic Resonance Chemical Shift Of the Carbonymentioning
confidence: 71%
“…This reversal in the trend of substituent effects, particularly electronic ones, on δ co and acidity parameters (log K /log k +1 ) of benzoic acids reflects significant differences in the transmission modes of substituents' electronic effects. These authors obtained the following statistically well‐significant correlations for substituent effects on δ co in benzoic acids: δnormalcnormalo0.25em()chloroformd6=4.81σI2.05σRBA+172.88 δnormalcnormalo0.25em()chloroformd=3.38σI+1.11σRBA+172.01 normalc.normalf.0.25emnormallogk+10.25em()toluene=6.14σI+2.51σRBA+1.84 for m ‐methyl‐substituents, methoxy‐substituents, phenoxy‐substituents, fluoro‐substituents, chloro‐substituents, bromo‐substituents, iodo‐substituents, benzoyl‐substituents, trifluoromethyl‐substituents, nitro‐substituents, and hydrogen substituents following Taft's dual‐substituent parameter model with substituent coefficients from Charton's compilation; δnormalcnormalo0.25em()benzened6=6.37σI+1.82v+173.19 δnormalcnormalo0.25em()chloroformd=5.43σI+1.35v+172.34 normalc.normalf.0.25emnormallogk+1…”
Section: C Nuclear Magnetic Resonance Chemical Shift Of the Carbonymentioning
confidence: 94%
See 2 more Smart Citations